1995
DOI: 10.1128/aem.61.1.310-316.1995
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of arginine deiminase pathway enzymes in arginine catabolism by wine lactic Acid bacteria

Abstract: L-Arginine, an amino acid found in significant quantities in grape juice and wine, is known to be catabolized by some wine lactic acid bacteria. The correlation between the occurrence of arginine deiminase pathway enzymes and the ability to catabolize arginine was examined in this study. The activities of the three arginine deiminase pathway enzymes, arginine deiminase, ornithine transcarbamylase, and carbamate kinase, were measured in cell extracts of 35 strains of wine lactic acid bacteria. These enzymes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 36 publications
2
64
0
1
Order By: Relevance
“…These enzymes could not be detected in L. helveticus (data not shown). Recently, Liu et al [14] reported the presence of arginine deimidase in hetero-fermentative but not in homo-fermentative lactobacilli. Our results are consistent with this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…These enzymes could not be detected in L. helveticus (data not shown). Recently, Liu et al [14] reported the presence of arginine deimidase in hetero-fermentative but not in homo-fermentative lactobacilli. Our results are consistent with this conclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Another relevant finding was the reduction or disappearance of arginine during the manufacture of the ciders studied, which could be explained in function of the complex microbiological interactions along natural cider production, as alcoholic and MLF occur simultaneously, and microbiological stabilization is not performed. Thus, high levels of heterofermentative LAB found after MLF (Duen˜as et al, 1994) might degrade this amino acid via the arginine deiminase pathway, producing citrulline and carbamyl phosphate (Liu et al, 1995). In addition, it has also been described that some yeast could also degrade this amino acid producing urea and other carbamylic compounds as intermediates of arginine metabolism.…”
Section: Microbiota and Evolution Of Fermentationsmentioning
confidence: 99%
“…Resting cell experiments were performed according to Mira de Ordun ¬ a et al [16] with modi¢cations. Bacterial cells were grown in 500 ml of a complex medium (TJAG [17], without addition of arginine) at 30³C to the late-exponential phase and harvested by centrifugation at 5000Ug for 10 min at 15³C. Yeast cells were grown in 500 ml YM broth (Difco, Detroit, MI, USA).…”
Section: Culture Conditions and Resting Cell Experimentsmentioning
confidence: 99%